2010
DOI: 10.1021/cg9012813
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of All Crystalline Phases of Anhydrous Calcium Carbonate

Abstract: Usually, the metastable vaterite phase transforms to the thermodynamically most stable calcite phase. We report here the phase transformation of vaterite to aragonite, which is seldom observed in the synthetic processes of calcium carbonate. The vaterite, upon equilibration with distilled water at room temperature, gradually transforms to aragonite. This transformation process is further accelerated when the vaterite sample is refluxed in distilled water. Under a different set of conditions, when equilibrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 57 publications
7
66
0
3
Order By: Relevance
“…The comparison of the most intensive peaks presented in Table 2 reveals that rhombohedrals are calcite, while the spherical polycrystalline particles are vaterite in accordance with other studies [32]. It is important to point out that the slow phase transition of vaterite into calcite does not occur within the time frame of our experiments [33].…”
Section: Reference Spectrasupporting
confidence: 89%
“…The comparison of the most intensive peaks presented in Table 2 reveals that rhombohedrals are calcite, while the spherical polycrystalline particles are vaterite in accordance with other studies [32]. It is important to point out that the slow phase transition of vaterite into calcite does not occur within the time frame of our experiments [33].…”
Section: Reference Spectrasupporting
confidence: 89%
“…3, the peak at $133 cm À1 in XL1-1 showed a transition phase indicating which peak of vaterite at $120 cm À1 shifts to peak at $141 cm À1 of aragonite. Similarly, the peak at $178 cm À1 in XL1-1 showed a [19,[34][35][36]. In the present work, it is proposed that the vaterite could be the precursor of aragonite phase of coral skeleton from South China Sea.…”
Section: Raman Spectroscopysupporting
confidence: 53%
“…Pure vaterite (≥ 99 wt.%) was found at 60°C. Only few studies can be found that deal with the synthesis of vaterite with the same reactants [28,29]. Sarka et al [29] have synthesized pure vaterite at 30°C with 200 rpm stirring velocity.…”
Section: Resultsmentioning
confidence: 99%
“…Only few studies can be found that deal with the synthesis of vaterite with the same reactants [28,29]. Sarka et al [29] have synthesized pure vaterite at 30°C with 200 rpm stirring velocity. This difference is probably caused by the modified experimental set up, mainly by the usage of a smaller volume of reactants, which actually diminishes the total reaction time, and variant impeller.…”
Section: Resultsmentioning
confidence: 99%